2012
DOI: 10.5194/bgd-9-12433-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of four decades of annual nitrogen addition on dissolved organic matter in a boreal forest soil

Abstract: Addition of mineral nitrogen (N) can alter the concentration and quality of dissolved organic matter (DOM) in forest soils. The aim of this study was to assess the effect of long-term mineral N addition on soil solution concentration of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) in the Stråsan experimental forest (Norway spruce) in Central Sweden. N was added yearly at two levels of intensity and duration: the N1 treatment represented a lower intensity, but a longer duration (43 y… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Short-term N additions in different forests have shown distinct responses of SUVA to N addition. 36,44 However, the present results coincide with an earlier finding that 4 decades of N addition increased the SUVA of soil-derived DOM in B horizons but not in O horizons in a boreal forest 75 and another finding that SUVA and soluble phenols in soil DOM at 75 cm were all increased at four different forests with 10 years of N addition. 45 Furthermore, the average E2/E3 ratios were consistently lower in the N-added soils than those in control soils in all horizons (Figure 1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Short-term N additions in different forests have shown distinct responses of SUVA to N addition. 36,44 However, the present results coincide with an earlier finding that 4 decades of N addition increased the SUVA of soil-derived DOM in B horizons but not in O horizons in a boreal forest 75 and another finding that SUVA and soluble phenols in soil DOM at 75 cm were all increased at four different forests with 10 years of N addition. 45 Furthermore, the average E2/E3 ratios were consistently lower in the N-added soils than those in control soils in all horizons (Figure 1).…”
Section: Resultssupporting
confidence: 90%
“…While several studies have hypothesized that DOM may respond differentially to the long-term addition, 36,44,45,75 this study identified previously unreported shifts in DOM composition with long-term N addition. After 22 years of N addition, soil-derived DOM exhibited a minor increase in its storage (an increase of ∼10%) but had significant alterations in its optical properties and molecular-level composition.…”
Section: Dom Composition Based On Ft-icr Msmentioning
confidence: 56%
“…Xu et al conducted an N addition experiment in a mixed forest by using Korean pine and broadleaf at Changbai Mountains, but suggested that N addition decreased the concentration of DOC in soil solutions at 60 cm depth [ 16 ]. Conversly, Rappe-George et al found that the concentration of DOC in soil solution in the O’ horizon was similar between N treatments and control [ 17 ]. Thus, the effect of warming and N deposition on DOM remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of DOC concentrations in forest floor and soil leachates to N addition have been shown to be inconsistent among different studies (X. Lu et al., 2013; McDowell et al., 2004; Pregitzer et al., 2004; Rappe‐George et al., 2013). These contrasting responses have been attributed to the differences in the N status of forest ecosystems (X. Lu et al., 2021), the type and dose (i.e., application rate) of N fertilizer (Evans et al., 2008; Liu & Greaver, 2010), the duration of N addition and the place of leachate collection (Hagedorn et al., 2012; Rappe‐George et al., 2013). Our results in the N‐limited montane forest supported these findings as well as our second hypothesis that the N addition affected the concentrations, fluxes, SUVA 285 and biodegradability of DOC in leachates, while the effects were dose and soil depth dependent (Figures 2–5).…”
Section: Discussionmentioning
confidence: 99%
“…Leaching of DOC as an alternative important pathway of soil C loss has been less well characterized than the effects on soil respiration in N addition experiments. A limited number of available studies showed that the response of leached DOC concentrations and fluxes in response to N addition could be either positive, negative, or neutral (Chang et al., 2018; X. Lu et al., 2013; McDowell et al., 2004; Pregitzer et al., 2004; Rappe‐George et al., 2013; Xu et al., 2021). To reconcile these inconsistent results, it is necessary to understand the processes controlling the balance between DOC generation and depletion and how these processes are affected by N addition.…”
Section: Introductionmentioning
confidence: 99%